The German Cockroach - P.G. Koehler; J.L. Castner (EDIS)
This document provides an overview of the German cockroach, the most significant cockroach species in the United States. It details the life cycle from egg to adult, highlighting the differences between males and females, their reproductive habits, and the development of oothecae (egg capsules). The document also describes the various nymph stages and the conditions that favor cockroach infestations, such as the availability of food, water, and shelter. The publication emphasizes the importance of understanding these factors for effective pest management. Date first printed: January 1994.